Analysis of the anaerobic power output, dynamic stability, lower limb strength, and power of elite soccer players based on their field position - Al Taweel, A.; Nuhmani, S.; Ahsan, M.; Al Muslem, W. H.; Abualait, T.; Muaidi, Q. I. (healthcare, 2022)
Soccer players require a high degree of aerobic and anaerobic fitness to perform well throughout the game as per their position in the field. This study aimed to investigate the differences in anaerobic power output, dynamic stability, lower limb strength, and power among elite soccer players based on their field position. A cross-sectional population of 96 elite soccer players with average age 23.10 ± 4.35 years, weight 69.99 ± 9.71 kg, height 174.84 ± 6.64 cm, and body mass index 22.84 ± 2.39 kg/m2 from various soccer clubs in Saudi Arabia was tested for their anaerobic power output, dynamic stability, lower limb strength, and power performance. All the participants have more than 4 years of experience in competitive soccer events. Tests included a measure of single-leg vertical jump, star excursion balance test, and single-leg triple hop test for distance. The players were divided into four groups (goalkeepers, defenders, midfielders, and attackers) based on their self-reported position on the field. One-way ANOVA was used to determine the differences between all variables according to the players` position. In addition, partial eta-squared (Etap2) was used to report effect sizes. The results revealed significant differences between positions in the anaerobic power output (p = 0.012, Etap2 = 0.312), dynamic stability {Anterior (p = 0.004, Etap2 = 0.235), Anteromedial (p = 0.007, Etap2 = 0.622), Anterolateral (p = 0.011, Etap2 = 0.114)}, and lower limb strength, and power (p = 0.008, Etap2 = 0.421). At the same time, goalkeepers` performance was significantly superior to midfielders (p = 0.006) in the anaerobic power output. In addition, lower limb strength and power was significantly higher (p = 0.004) for goalkeepers than for midfielders, with a similar trend in dynamic stability (p = 0.007). These results exhibited differences in anaerobic power output, dynamic stability, lower limb strength, and power performance based on the players` positions. The investigation may assist the practitioner in designing training programs for the players according to their position for performance improvement.